2004
DOI: 10.1074/jbc.m410144200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinase 1 (SPHK1) Is Induced by Transforming Growth Factor-β and Mediates TIMP-1 Up-regulation

Abstract: Transforming growth factor-␤ (TGF-␤) signaling plays a pivotal role in extracellular matrix deposition by stimulating collagen production and other extracellular matrix proteins and by inhibiting matrix degradation. The present study was undertaken to define the role of sphingosine kinase (SphK) in TGF-␤ signaling. TGF-␤ markedly up-regulated SphK1 mRNA and protein amounts and caused a prolonged increase in SphK activity in dermal fibroblasts. Concomitantly, TGF-␤ reduced sphingosine-1-phosphate phosphatase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 44 publications
8
117
0
1
Order By: Relevance
“…It has been observed that TGF-β increases Sphk1 activity and upregulates mRNA and protein levels of Sphk1 in dermal fibroblasts [74]. Thus, it is hypothesized that crosstalk between TGF-β and S1P regulates MMP expression.…”
Section: S1p and Tgf-β/smad3 Crosstalk In Wound Healingmentioning
confidence: 99%
“…It has been observed that TGF-β increases Sphk1 activity and upregulates mRNA and protein levels of Sphk1 in dermal fibroblasts [74]. Thus, it is hypothesized that crosstalk between TGF-β and S1P regulates MMP expression.…”
Section: S1p and Tgf-β/smad3 Crosstalk In Wound Healingmentioning
confidence: 99%
“…Because ectopically expressed proteins may not always exactly mimic the localization and functions of their endogenous counterparts, it was important to establish the involvement of endogenous SphK1 and SphK2 in regulation of ceramide levels. To this end, we utilized small interfering RNA targeted to a specific sequence of SphK1 that has been successfully used to down-regulate SphK1 protein and activity (19,32,(57)(58)(59). As expected, down-regulation of SphK1 with small interfering RNA significantly reduced SphK1 protein levels, mRNA, and enzymatic activity (Fig.…”
Section: Sphk2-induced Apoptosis Depends On Ca 2ϩmentioning
confidence: 99%
“…BDL itself activated both MMP-9 and MMP-2 to a lesser extent. TIMP-1 is an endogenous inhibitor of MMPs and is regulated by SphK activity in human fibroblasts, 12 raising the possibility that it may play a role in the protective effects of SphK1. In our model, TIMP-1 mRNA was increased in the ligated left lobe in WT mice (Fig.…”
Section: Apoptotic Effect Of Tnf-␣ In Nf-b-suppressed Liver In Bdl MImentioning
confidence: 99%
“…10,11 SphK1 is also involved in the regulation of tissue inhibitor of metalloproteinase 1 (TIMP-1) in fibroblasts. 12 TIMP-1 inhibits MMP-9 and MMP-2. 13 However, the role of SphK in activated HSCs is unknown.…”
mentioning
confidence: 99%